FACTORS THAT DISADVANTAGE THE INCREASE OF PEOPLE'S ABILITY TO COOPERATE WITH LIFE'S CHALLENGES - Suyunov Odiljon Orif o`g’li (European Science Publishing, 2025)
The article examines factors that weaken people's ability to cope with life's difficulties.
Keywords: Social isolation, social helplessness, childhood trauma, depression and anxiety, genetic predisposition, social stigma.